Dry Season Study of Arthropods’ Succession on Pig Carrions in Edjeba, Nigeria - P.E., ODO (International Journal of Scientific Research in Biological Sciences, 2021)
Arthropods’ succession on putrefying pigs were monitored at the Edjeba community in Southern Nigeria, from 10th June to 10th August 2018. The arthropods were collected with the aid of sweep nets while the bodies of the carrions and the soil below the carrions were combed with brushes for the presence of the arthropods two times for the first week and one time for the remaining weeks, insects’ maggots found were grown till adults. Multiple bar charts were applied to illustrate the regularities of the flies in every phase of decay, pie charts were used similarly to indicate phases of putrefaction, Component bar charts were applied to demonstrate succession of the different orders of insects, while Principle Component Analysis (PCA) was used to show the spreading of insects in the different decay phases. Whereas PCA indicates that constituent 1 stood for 47.9% of the disparity in the dataset, constituent 2 stood for 30.8% making a total of 78.7%. The Simpson index was high (0.94) in the active decay phase but low (0.87) in the fresh phase. The dominance index was high (0.13) in fresh phase but low (0.06) in active decay phase, Shannon–Wiener index (H) was high (2.96) in the active decay phase but low (2.19) in the fresh phase. The evenness index (E) was high (0.92) in active decay phase but low (0.75) in dry decay phase and Margalef (R) was high (3.32) in advanced decay phase but low (1.88) in fresh phase. The equitability index was high (0.97) in active decay phase but low (0.89) in dry decay phase. The total number of insects collected were 1495, 244 were at fresh phase of decay, 273 at bloated phase, 437 at active decay phase and 346 at advance decay phase and 195 at dry decay phase of decay as 1090 of these insects were Diptera, Coleoptera were 285 and only 110 were Hymenoptera. More studies on carrion ecology should be carried out in the Edjeba community and its environs in order to generate trustworthy data base of arthropods of forensic importance in the city.